Making Sense of Antisense - Bruce R Yacyshyn; William R Shanahan (Canadian Journal of Gastroenterology)
Since the identification of the DNA double-stranded helix, the gene as a target of therapy and, moreover, the use of DNA as a drug have been possibilities. ‘Antisense’ is used by some living organisms, specifically viruses, to control gene replication. Only recently, the use of antisense DNA as a mechanism to control human gene translation has been appreciated. A recent report on the use of systemically administered oligonucleotides in human Crohn’s disease is reviewed. DNA antisense oligonucleotides offer a technology capable of unique use at the laboratory bench as well as for highly specific therapeutic drugs. The conceptualization and possible future directions of these exciting compounds are reviewed.